A case report on mushroom poisoning: modern insights into an age-old problem - Limbu, Adarsh (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Mushroom poisoning is a common toxicological emergency in Nepal during the monsoon season, often due to the misidentification of wild mushrooms. This report presents a case of accidental poisoning in a family of three who developed gastrointestinal and neurological symptoms after consuming foraged mushrooms. Clinical findings suggested hallucinogenic Psilocybin species as the likely cause. With supportive care—including IV fluids, anti-emetics, and sedatives—all three recovered fully within 24 hours. The case highlights the diagnostic challenges posed by hallucinogenic mushrooms and identifies the potential role of Artificial intelligence (AI) based tools in aiding mushroom identification, particularly in resource-limited settings. The integration of such technologies, along with standardized guidelines, could enhance early recognition and improve outcomes in mushroom poisoning cases.